Diagnostic value of effusion adenosine deaminase, γ-interferon release assay and effusion lactatedehy drogenase/effusion adenosine deaminase for tuberculous pleural effusion in patients aged 60 years and above - Huimin, Chen; Xia, Wei; Xu, Yilin; Jin, Weijiang; Liu, Fang (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundChina is experiencing rapid growth in its population of older adults, which may lead to increased susceptibility to tuberculous pleural effusion (TPE) due to age-related changes in the immune system. This study aimed to investigate the diagnostic potential of multiple biomarkers in individuals aged 60 years and above with pleural effusion.MethodsA total of 519 adult patients from Ningbo First Hospital were included in the study, with 7 biomarkers and their ratios in serum and pleural effusion analyzed using logistic regression analysis. Effusion Adenosine Deaminase(ADA), γ-Interferon Release Assay(IGRA), and Effusion lactatedehy drogenase(LDH)/Effusion ADA were identified as valuable parameters for differentiating TPE from non-TPE, particularly in individuals aged 60 years and older.ResultsEffusion ADA, IGRA, and Effusion LDH/Effusion ADA were identified as valuable parameters for the differential diagnosis of TPE from non-TPE, showing good diagnostic performance in individuals aged 60 years and older. The combined diagnosis of these three indexes achieved the highest diagnostic accuracy for TPE in this age group, with an AUC of 0.925, sensitivity of 85.23%, and specificity of 89.57%.ConclusionsOverall, the study highlights the importance of using multiple indicators for a combined diagnosis to improve diagnostic efficacy in detecting tuberculous pleurisy in older individuals as for young patients.